Analisis Semiotika Roland Barthez Pada Terapi Zikir Menghadapi Pandemi Covid 19 di Pondok Pesantren Singa Putih Munfaridin - Dianis Nurwati (Program Studi Ilmu Komunikasi, 2023)
Singa Putih is one of the Islamic Boarding School in the Pasuruan area of East Java. Amid the strengthening of the impact of stress on society due to the spread of the covid virus 19 Singa Putih Islamic Boarding School is also present in an effort to provide health education to the public. This education is a form of communication in the form of both verbal and non-verbal which is summarized in the activities of zikir therapy accompanied by body movements. The process of therapy activities accompanied by body movements requires semiotic analysis to reveal the interpretation of each non-verbal movement. This study aims to conduct an interpretive analysis related to the meaning of health messages in dhikr therapy against Covid 19. Publication of therapy activities through youtube media is used to collect data in the form of screenshots, documentation and literature studies. The results of this study divided the level of meaning of zikir therapy into two parts, namely denotative and connotative meaning to reveal the mythology that exists in therapy activities.